High temperature corrosion of SAC 405 solder alloy - Cruz, Noelle Easter Villanueva
Recent advances in the microelectronics industry are accompanied by the increase in the environmental awareness of the consumers thus semiconductor manufactures need to comply with such environmental policies. SAC 405 alloy is developed as an alternative for the Sn-Pb solder. This study utilizes the Tafel method to determine the corrosion current of the SAC 405 in water, NaCI and H2SO4 electrolytes at temperatures 25°C, 40°C and 60°C. Increase in acid concentration shifts the cathodic portion of the Tafel plots, while the anodic portion of the Tafel plots remains unaffected. An increase in salt concentration doesn't have an effect on the cathodic portion of the Tafel plot, thus it has no effect on corrosion current. The cathodic portion of the Tafel plot can not be used to generalize the corrosion mechanism of SAC 405 alloy in NaCI due to the passivation mechanism involved. The increase in salt concentration makes the active to passive transition region of the Tafel plot more defined. The increase in temperature has an effect on the corrosion current reading for the H2SO4 electrolyte but not for the NaCI. The relationship between the corrosion current and the activities of the corrosive species in the aqueous systems is established to determine the reaction order using the principles in aqueous metallurgical thermodynamics. Determination of the activity of H+ ion using Debye-Huckel extended law is more accurate for the purpose of determining the reaction order of the system.